DEVELOPMENT OF A FLOATING PV POWER PLANT LAYOUT DESIGN OPTIMIZATION SYSTEM USING GENETIC ALGORITHMS - Fauzan Nadhif, Ahmad
Indonesia faces an increasing demand for electricity, driving the development of renewable power sources such as Solar Power Plants (PLTS). One solution to address land constraints is utilizing water bodies for the installation of Floating Photovoltaic (FPV) systems. The design and layout of FPVs require special attention as they impact the capacity, cost, and operation of the power plant. Therefore, it is crucial to optimize the FPV layout design by considering technical requirements and existing environmental data. To achieve an optimal layout design, two optimization methods are employed: the grid-cell first fit method and the array-polygon genetic algorithm method. The grid-cell first fit method, which divides the land into discrete grid cells, offers a deterministic solution but is limited in orientation flexibility. In contrast, the more flexible array-polygon genetic algorithm method generates stochastic solutions of comparable quality and can be adjusted for FPV orientation. In a case study on the Duriangkang Reservoir in Batam, the array-polygon genetic algorithm method was chosen, resulting in a design that utilized 29.27% of the available area with an annual power capacity of 1,090.12 GWh and estimated profit of Rp40,303,901,410,748.